Analysis of Chest Tube Scars on the Use of Conventional versus Knotless Methods - Claudia Loho; Mendy Hatibie; Adrian Tangkilisan; Wega Sukanto; Fredrik G. Langi (e-CliniC, 2022)
Abstract: Removal of chest tube is a one of the most distressing and frustrating experience for patients. Moreover, it has a tendency of scar formation. A relatively new method has been developed using a type of suture without knots (knotless). Assessment of scar is an objective and subjective method performed by using patient and observer scar assessment scale (POSAS). This study was aimed to assess the scars formed due to chest tube removal using conventional and knotless sutures. This was a controlled trial design. The Mann-Whitney test was used to compare the PSOAS scores of scars formed due to conventional and knotless sutures performed by patients and observers after three months, and obtained a p-value of less than 0.05. In conclusion, scar formation due to knotless suture is more acceptable for patients compared to conventional suture among chest tube removal wounds; therefore, the knotless suture can be a cosmetically alternative for wound closure management. Keywords: chest tube; scar tissue; knotless suture; conventional sutureÂ Abstrak: Pelepasan chest tube merupakan hal yang menyakitkan dan pengalaman yang membuat frustasi bagi pasien. Selain itu, tindakan ini berpeluang menyebabkan pembentukan jaringan parut. Telah dikembangkan metode baru dengan material jahitan baru yang tidak perlu disimpul. Penilaian jaringan parut dapat berupa penilaian obyektif dan subyektif dengan menggunakan Patient and Observer Scar Assessment Scale (POSAS). Penelitian ini bertujuan untuk menilai jaringan parut akibat pelepasan chest tube antara penjahitan metode konvensional dan knotless. Desain penelitian ialah controlled trial. Penilaian PSOAS baik dari pasien, observer, atau keduanya dilakukan tiga bulan kemudian terhadap jaringan parut yang terbentuk akibat penggunaan kedua metode. Perbandingan hasil skor PSOAS dianalisis dengan uji Mann-Whitney yang mendapatkan nilai p<0,05. Simpulan penelitian ini ialah pembentukan jaringan parut pada metode knotless lebih akseptabel bagi pasien dibandingkan metode konvensional. Hal ini dapat menjadi salah satu metode alternatif penutupan luka chest tube dengan hasil yang lebih dapat diterima.Kata kunci: chest tube; jaringan parut; metode knotless; metode konvensional